Enhancing ovarian cancer care: a systematic review of guideline adherence and clinical variation - Kahren M. White; Holly Seale; Reema Harrison (BMC, 2019)
Abstract Background Clinical variation in ovarian cancer care has been reported internationally. Using Wennberg's classification of clinical variation as effective care we can conceptualise variation through deviation from clinical guidelines. The aim of this review was to address knowledge gaps in the effectiveness of attempts to reduce unwarranted clinical variation through addressing the following questions: What is the evidence of guideline adherence in ovarian cancer and its deviation?; what are the key factors associated with variation in guideline adherence in ovarian cancer care?; and what quality improvement approaches have been used and what is the evidence of their effectiveness in enhancing guideline adherence in ovarian cancer care?. Methods Keywords and synonyms for the major concepts of ovarian cancer, guideline adherence and safety were developed and combined to form the search strategy. Systematic searches of four electronic databases were undertaken of publications from January 2007 to November 2018. Retrieved articles were assessed against the eligibility criteria to determine those for inclusion. Results Thirty-two papers were included in the review with three broad groupings identified: adherence to and deviation from guidelines (either local, national or international guidelines); factors impacting guidelines adherence; and quality improvement approaches. Conclusions Unwarranted clinical variation may be used as a marker for the effectiveness of a health system, based on the outcome of this systematic review. This review found that the implementation of quality indicators through a formal quality improvement program lead to improvements in guideline adherent care. Further research on outcomes of implementing quality improvement programs in ovarian cancer care will improve the ability to implement centralised care and further identify factors that to improve outcomes in ovarian cancer care.